High-throughput optofluidic screening of single B cells identifies novel cross-reactive antibodies as inhibitors of uPAR with antibody-dependent effector functions - André Luiz Lourenço; Shih-Wei Chuo; Markus F. Bohn; Byron Hann; Shireen Khan; Neha Yevalekar; Nitin Patel; Teddy Yang; Lina Xu; Dandan Lv; Robert Drakas; Sarah Lively; et al. (mAbs)
The urokinase-type plasminogen activator receptor (uPAR) is an essential regulator for cell signaling in tumor cell proliferation, adhesion, and metastasis. The ubiquitous nature of uPAR in many aggressive cancer types makes uPAR an attractive target for immunotherapy. Here, we present a rapid and successful workflow for developing cross-reactive anti-uPAR recombinant antibodies (rAbs) using high-throughput optofluidic screening of single B-cells from human uPAR-immunized mice. A total of 80 human and cynomolgus uPAR cross-reactive plasma cells were identified, and selected mouse VH/VL domains were linked to the trastuzumab (Herceptin®) constant domains for the expression of mouse-human chimeric antibodies. The resulting rAbs were characterized by their tumor-cell recognition, binding activity, and cell adhesion inhibition on triple-negative breast cancer cells. In addition, the rAbs were shown to enact antibody-dependent cellular cytotoxicity (ADCC) in the presence of either human natural killer cells or peripheral blood mononuclear cells, and were evaluated for the potential use of uPAR-targeting antibody-drug conjugates (ADCs). Three lead antibodies (11857, 8163, and 3159) were evaluated for their therapeutic efficacy in vivo and were shown to suppress tumor growth. Finally, the binding epitopes of the lead antibodies were characterized, providing information on their unique binding modes to uPAR. Altogether, the strategy identified unique cross-reactive antibodies with ADCC, ADC, and functional inhibitory effects by targeting cell-surface uPAR, that can be tested in safety studies and serve as potential immunotherapeutics.